The initiatives takeb ny the 2018 Cape Town Cycle Tour to ensure a positive participant-experience despite facing water scarcity in the Western Cape: a qualitative study focusing on sports branding - Montgomery, Kate (The IIE, 2018)
This study aims to establish whether the initiatives implemented by the organisers of the Cape Town Cycle Tour (henceforth referred to as the Cycle Tour) to purchase and circulate two-million litres of water into the Western Cape municipal grid were successful in keeping a positive brand image and positive participant experience in general. Using a qualitative approach, the researcher sent an electronic questionnaire to twenty-five participants. The questionnaire consisted of ten questions, including both open-ended and closed-ended questions. The researcher then used a qualitative approach of line-by-line coding in order the analyse the data. The study found that after the implementation of the initiatives the brand image and identity of the 2018 Cycle Tour remained aligned. The paper also found the that due to the Cycle Tour showing awareness of the water crisis and implementing water saving measures, the impact on the brand was positive. The findings confirm that a brand’s awareness of the environment and long-term sustainability, has a positive impact on the brand. Results such as these raise awareness that the sporting and events world need to be more environmentally conscious in the future.
Keywords: Brand image; Brand identity; Brand awareness; Healthy brand; Brand health; Sports branding